Effect of Cavity Disinfection with Chlorhexidine on Marginal Gap of Class V Composite Restorations Bonded with a Universal Adhesive Using Self-Etch and Etch-and-Rinse Bonding Strategy - Soodabeh Kimyai; Narmin Mohammadi; Mahmoud Bahari; Elahe Pesyanian; Farhood Pesyanian (Tehran University of Medical Sciences, 2020)
Objectives: This in-vitro study aimed to evaluate the effect of cavity disinfection with chlorhexidine (CHX) on marginal gaps of Class V composite resin restorations bonded with a universal adhesive using self-etch and etch-and-rinse bonding strategy. Materials and Methods: Sixty sound human premolars were randomly assigned to two groups (n=30): group 1 (CHX) and group 2 (no CHX). Each group was divided into two subgroups (n=15) according to the bonding strategy of the universal adhesive (self-etch or etch-and-rinse). Class V cavities were prepared on the buccal surfaces of the teeth. The occlusal and gingival margins of the cavities were placed in enamel and dentin, respectively. In the first and second subgroups of both groups, the All-Bond Universal adhesive was applied with self-etch and etch-and-rinse bonding strategy, respectively. After restoration and thermocycling, the samples were sectioned, and marginal gaps at the gingival margins were measured in micrometer (µm) under a stereomicroscope. Two-way analysis of variance (ANOVA) was used to compare marginal gaps between the groups and the subgroups. Results: The mean marginal gap size was significantly affected by cavity disinfection (P=0.001) and bonding strategy (P=0.002). However, the interaction effect of these two factors on the mean marginal gap size was not significant (P=0.79). Conclusion: The use of CHX resulted in larger marginal gaps at the gingival margins of Class V composite resin restorations. Irrespective of disinfection, the self-etch bonding strategy resulted in larger marginal gaps compared to the etch-and-rinse bonding strategy.